Accelerated Stability Test of Snakehead Fish Extract (Channa striata) and Kelulut Honey (heterotrigona itama) Ointment Combination with Tween 80 and Span 80 as an Emulsifying Agent - Wintari Taurina; Mohamad Andrie; Taufik Nanda Pratama (Majalah Obat Tradisional, 2021)
The combination of Snakehead Fish and Kelulut Honey has activity in accelerating the wound healing process. The ointment with active ingredients of Snakehead Fish extract and Kelulut Honey showed separation from the active ingredient and its base. The addition of tween 80 and span 80 is expected to increase the stability of the ointment preparation by keeping the water-phase droplets distributed uniformly on the ointment base. This study aimed to determine the effect of adding Tween 80 and Span 80 on the stability of the ointment preparation. The ointment was made by varying Tween 80 and span 80 by 2,5%: 5%: 7,5% and control (active ingredients without the addition of tween 80 and Span 80) as a comparison. The preparation was subjected to an accelerated stability test using a temperature of 40 ° ± 2 ° C / Relative humidity 75% ± 5% for 28 days by observing the organoleptic test, adhesion, spreadability, homogeneity test, pH test, and protection power. The data obtained were analyzed statistically using One Way Anova. The analysis showed that the addition of tween 80 and span 80 with a total concentration of 5% and 7,5% had a significant effect in increasing the spreadability, decreasing adhesion, and reducing the pH of the preparation. Formulas that meet the requirements in this study are F2 and F3, which have an average spreadability of 5,11 cm and 5,25 cm, adhesion of 96 seconds and 51 seconds, and pH of 6,02 and 5,02.